Sabzian : Sabzian is a collection of online reflections on cinema and maps cinephile events in Belgium and surroundings : #2. - Claes, Gerard-Jan; Grootaers, Elias ([S.l.] : Sabzian, 2015)
Some Came Running ; Op weg naar een sociale cinema ; Fragmenten van Dirk Lauwaert
boek